Projeto de um tribômetro para ensaio de atrito e desgaste rotativo ou linear recíproco - Rosa, Bruno Barioni Ribeiro (2025)
In the competitive industrial scenario, the search for innovative solutions that provide quality, efficiency, and durability to machines and equipment has demanded investment in research and testing of new materials, components, or lubricants before prototype construction. In this context, tribometers, equipment for testing friction, wear, lubricants, and lubrication regimes, are essential for preliminarily and comparatively analyzing different tribological alternatives under various loading conditions, types of motion, rotation/speed, lubrication, and temperature. The main objective of this work is the development of a low-cost pin-disc type tribometer design aimed at academic applications, with the unique feature of being capable of performing the tests established in ASTM G99-17 and ASTM G133-22 standards. The designed tribometer has two interchangeable modules that allow for performing either rotary or reciprocating linear tests between the tested elements, varying load, rotation, and lubrication condition. The designs and specifications of all components that make up the designed tribometer are presented at the end of the work and the expectation is that the construction and application of the tribometer will enable the development of teaching and research activities in Higher Education Institutions, contributing to the improvement of the training of undergraduate and graduate students in the field of engineering, as well as the development of technological solutions that can bring economic benefits to the industry and society in general.